2024
DOI: 10.1111/dom.15475
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acid levels are inversely associated with incident and prevalent chronic kidney disease in people with type 2 diabetes

Juliette A. de Klerk,
Roel Bijkerk,
Joline W. J. Beulens
et al.

Abstract: AimTo investigate the association of plasma metabolites with incident and prevalent chronic kidney disease (CKD) in people with type 2 diabetes and establish whether this association is causal.Materials and MethodsThe Hoorn Diabetes Care System cohort is a large prospective cohort consisting of individuals with type 2 diabetes from the northwest part of the Netherlands. In this cohort we assessed the association of baseline plasma levels of 172 metabolites with incident (Ntotal = 462/Ncase = 81) and prevalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Circulating amino acids are closely associated with diabetes, obesity, cardiovascular disease, and many other chronic diseases. Previous research has demonstrated associations between circulating BCAAs ( 29 ), Gln, Glu ( 30 ), and amino acids in the tryptophan-kynurenine pathway ( 31 ) with the risk of diabetes and its complications. In the present study, significant alterations were noted in the serum levels of the Gln/Glu ratio, Tryp, Ala, Ser, Pro, Val, Ile, Lys, His, Cys, and Thre.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating amino acids are closely associated with diabetes, obesity, cardiovascular disease, and many other chronic diseases. Previous research has demonstrated associations between circulating BCAAs ( 29 ), Gln, Glu ( 30 ), and amino acids in the tryptophan-kynurenine pathway ( 31 ) with the risk of diabetes and its complications. In the present study, significant alterations were noted in the serum levels of the Gln/Glu ratio, Tryp, Ala, Ser, Pro, Val, Ile, Lys, His, Cys, and Thre.…”
Section: Discussionmentioning
confidence: 99%